Analysis of plasma lipid peroxidation and antioxidant enzymes status in patients of oral leukoplakia: A case control study - Srivastava, Kumar Chandan (J Int Soc Prev Community Dent, 2016)
AIMS AND OBJECTIVES: Imbalances between the oxidant-antioxidant status have been implicated in the pathogenesis of several diseases, including oral cancer. Mostly, all oral cancer lesions are preceded by a stage of premalignancy. The present study aims to evaluate lipid peroxidation and antioxidant status in the venous blood of patients with different clinicopathologic stages of leukoplakia. MATERIALS AND METHODS: A case control study was designed with the inclusion of 20 new cases of histopathologically proven leukoplakia of various clinical stages along with an equal number of positive and negative control individuals. The concentrations of thiobarbituric acid reactive substances and the activities of the antioxidant enzymes, namely superoxide dismutase, reduced glutathione, glutathione peroxidase, and catalase, were estimated in plasma using spectrophotometric methods. The data are expressed as mean ± SD. The statistical comparisons between and within the study groups were performed by one-way analysis of variance followed by post hoc analysis. Karl Pearson correlation was performed for the biochemical parameters within the group and between the groups. For statistically significant correlations, simple linear regression was performed. RESULTS: Significant enhanced lipid peroxidation (P < 0.001) with a decrease in antioxidants (P < 0.001) was observed in the venous blood of leukoplakia patients compared with positive as well as negative controls. Accordingly, significant (P < 0.001) pattern of progression in thiobarbituric acid reactive substances levels was observed at various clinical stages among patients of both control groups. Among enzymes, glutathione showed significant (P < 0.001) reduction along the stages on comparison with two control groups. CONCLUSION: Enhanced lipid peroxidation and compromised antioxidant defense in plasma indicate the development of oxidative stress. Among the antioxidant enzymes, reduced glutathione and glutathione Pperoxidase may play a decisive role in malignant transformation.